Training Urgency to Bridge the Digital Divide for Social Media Marketing Awareness and Adoption: Case of CBT Rural Homestay Operators Malaysia - Murniati, Dewi Eka; Abdul Razzaq, Abdul Rasid; Ismail, Affero; Mota, Luis (Journal of Technical Education and Training, 2023)
Despite the fact that using social media for arranging trips is becoming increasingly important, community-based tourism (CBT) of Malaysian rural homestay operators still heavily rely on traditional marketing platforms and third parties’ assistance to gain tourist attraction. Previous studies found a lack of awareness constraining social media marketing adoption in small enterprises. Hence, this study aims at exploring the awareness of homestay operators regarding the use of social media as a marketing tool in CBT of rural homestay operators in Malaysia. A survey study was done by using a semi-structured interview involving nine respondents from nine homestays across Johor, Malaysia. The data were analysed using thematic analysis. The findings show that the community still has low awareness of the digital divide as well as the unavailability of relevant human resources and technical expertise. It also indicated that the homestays’ operators still use Malay rather than English on their social media promotion and interaction, which restricts their chances to access global markets. It is critical for operators of homestays to improve their competencies to maintain their businesses and increase their level of market competitiveness. Therefore, this study constitutes an essential call for stakeholders’ attention to enhance CBT rural homestay operators’ awareness through effective training. Accordingly, it closes the digital gaps that challenge social media marketing awareness and hence encourages technology adoption in the community.